The Effect of Social Media on Interpersonal Communication Skills in Contemporary Society - Farman, Fizza; Ul Ain, Qurat; Shahzad, Waheed (JELLL, 2025)
This study looks into how social media affects college students' interpersonal communication abilities in today's world. Data were gathered through surveys and interviews with English and international relations students using a mixed-methods approach. According to quantitative findings, using social media more improves digital verbal fluency but has a detrimental impact on nonverbal expressiveness, listening comprehension, empathy, and face-to-face communication. This was corroborated by qualitative research, which revealed that students frequently prefer virtual communication and are less comfortable in face-to-face settings. According to the report, there is an increasing reliance on digital platforms, which might impede genuine human interaction. Social media seems to undermine emotional depth and natural contact in real-world situations, even as it promotes virtual connectivity. The results also imply that students frequently utilize digital messaging in place of in-person talks, which may result in a drop in social intelligence and the quality of relationships. The study emphasizes how crucial it is to strike a balance between digital communication and conventional social skills in order to preserve meaningful and productive human interactions.